Estimation of growth parameters of Jack mackerel Trachurus murphyicaught in Peru, from length frequency analysis - Díaz, Erich (2013)
This paper presents estimates of the von Bertalanffy growth parameters for Jack mackerel T. murphyicaught in Peruvian waters from 1972 to 2012, based on length frequency analysis. L ∞ was estimated from the maximum length observed throughout the history of the fishery, and was kept as a fixed parameter in the estimation of k obtained by fitting a growth curve to the monthly progression of modes. The estimated values were: L∞ = 81.6 cm and k = 0.167y -1 . It is highlighted that this k values is similar to those estimated by other authors for Peru, and is higher than those estimated for the T. murphyicaught off in Chile. These results suggest that T. murphyicaught in Peru has a faster growth rate than the T. murphyifrom Chile.